Odontogenic myxoma: diagnostic and therapeutic challenges in paediatric and adult patients$da case series and review of the literature - Kansy, Julia Katharina; Krol, Zdzislav (Journal of cranio-maxillofacial surgery, 2012)
Introduction Odontogenic myxomas are benign but locally invasive tumours originating from primordial mesenchymal tooth forming tissues which do not metastasise. We present a series of two paediatric and two adult cases and focus on differences in diagnostic and therapeutic approaches between children and adults based on our own experience and a critical review of the literature.
Available online 31 May 2011
Gesehen am 25.06.2018